Effect of cold water immersion used between games on muscle power and biomechanical parameters on rugby players - Takeda, M.; Sato, T.; Kawamoto, A.; Aizawa, S.; Kato, H.; Suhara, Y.; Yamaguchi, Y.; Radak, Z. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recently, cold water immersion (CWI) has been used in many athletes to facilitate recovery from the fatigue after the athletic training or competition. However, despite the facts that there are some evidences demonstrating the positive effects of CWI on athletic performance (Eston, 1999; Vaile, 2008), there are pros and cons regarding the effect of CWI on athletic performance. Particularly, effect of CWI on muscle power after the athletic competition accompanied by muscle damage with severe body contact like rugby game has not been clarified. This study examined the effect of CWI used between 7th rugby simulation trainings including severe body contact on muscle power and biochemical parameters on rugby players. Methods: Thirty top level of Japanese university rugby players aged 21.0 ± 1.8 years old randomly assigned to any of 3 groups, i.e. 5 minutes CWI group (5-min. CWI, n = 10), 10 minutes CWI group (10-min. CWI, n = 10) and no CWI group (control, n = 10). Seventh rugby simulation training was performed including 1 severe tackle within 20 m dash, totally 12 tackles with 1,300 m dash. Total time of this training was 16 minutes (two 7 minutes consecutive training including 2 minutes half time rest). Ten seconds maximum bicycle pedaling power, 10 m dash time, vertical jump, grip strength, reaction time, and 20 seconds side step and biochemical parameters such as lactate dehydrogenase, creatine kinase, y-glutamyltranspeptidase , creatinine, sodium, chlorine, potassium, and white blood cell, and subjective fatigue were measured at pre training, post training, and post CWI with 2 hours rest. Results: Analysis of variance revealed no significant deteriorated effect of 7th rugby simulation training (pre training vs post training) in all variables in all 3 groups. As to the changes from post training to post CWI, only creatinine significantly reduced from post training to post CWI in 10-min CWI (-0.138±0.041) group compared 5-min CWI (-0.097±0.041) and control (-0.075±0.037) groups. There were no significant differences in any of other variables. Discussion: Although significant decrease in creatinine at post CWI in 10-min CWI group might be positive effect of CWI in 2 hours break between 7th rugby simulation training. However, our study strongly demonstrated that there no positive physiological and subjective effects of CWI used in 2 hours break time between 7th rugby games.